2021
DOI: 10.1002/psp.2534
|View full text |Cite
|
Sign up to set email alerts
|

First wave of SARS‐COV2 in Europe: Study and typology of the 15 worst affected European countries

Abstract: Since 11 March 2020 when officially declared a global pandemic, Covid‐19 (or SARS‐COV2) has turned out to be a multifaceted disease differently affecting countries and individuals. What makes certain countries more vulnerable than others has attracted the interest of scientists from various disciplines. This paper intends to compare the impact of demographic parameters, population health conditions and policy actions on prevalence and fatality levels of Covid‐19 during the first 3 months since its declaration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…This observed variation can be explained by the different thresholds of hospitalization among different countries. 37,38 Our study also showed that biologics without immunomodulators were associated with decreased COVID-19-related hospitalization in patients with IBD. Several studies 11,39,40 described the rationale for trying anti-TNF therapies in COVID-19.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This observed variation can be explained by the different thresholds of hospitalization among different countries. 37,38 Our study also showed that biologics without immunomodulators were associated with decreased COVID-19-related hospitalization in patients with IBD. Several studies 11,39,40 described the rationale for trying anti-TNF therapies in COVID-19.…”
Section: Discussionsupporting
confidence: 55%
“…Our study indicated that the percentage of hospitalization differed in each country. This observed variation can be explained by the different thresholds of hospitalization among different countries 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…During January 2021, at the peak of the pandemic in the United States, 79% of the hospital beds at the ICUs were occupied by COVID-19 patients despite a general urge for available ICU capacities for other acute diseases and surgeries [12]. In Europe, the fatality of the pandemic during the first months of 2020 was high, with a case-fatality rate of 8.3% and 250 deaths per one-million citizens [13]. However, significant variations regarding deaths per million infections and the in-hospital case-fatality rate across the European countries were observed [13].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the fatality of the pandemic during the first months of 2020 was high, with a case-fatality rate of 8.3% and 250 deaths per one-million citizens [13]. However, significant variations regarding deaths per million infections and the in-hospital case-fatality rate across the European countries were observed [13]. The number of deaths per million citizens was lowest in Slovakia and highest in Belgium, while Germany was located in the middle [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation